Pengembangan Industri Halal Berbasis Zakat Produktif Terintegrasi Lembaga Keuangan Syariah - mahmudah sadiah; Fatchur Rohman; Khabib Solihin; Habiburrohman Aksa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to develop an increase in halal industrial areas by creating new entrepreneurs through the distribution of productive zakat which is integrated with sharia financial institutions as a further  integrated business development with business assistance partners. This research metode is qualitative with primary data through in depth interviews with sharia banking players, the sharia microfinance industry, academics, zakat institutions and business actors. Primary data was obtained through sharia banking product brochures and zakat institutions. The research results show that the development of halal industrial areas needs to be supported by various parties. In the aspect of providing initial capital for underprivileged people (poor poverty criteria) it is carried out by zakat amil institutions but it is not enough from zakat institutions alone, synergy is needed with sharia financial institutions souch as sharia banking and sharia microfinance institutions and also business partners/business (business consultant) for the success of distribution so that the halal industry continues to develop.